Ruxolitinib for the Treatment of Chronic GVHD and Overlap Syndrome in Children and Young Adults. Issue 2 (February 2022) - Wang, YunZu Michele; Teusink-Cross, Ashley; Elborai, Yasser; Krupski, M. Christa; Nelson, Adam S.; Grimley, Michael S.; Flannery, Amanda; Mehta, Parinda A.; Bleesing, Jacob J.; Chandra, Sharat; Kumar, Ashish R.; Myers, Kasiani C.; et al.
Abstract : Background: Ruxolitinib, a JAK1/2 inhibitor, is used to treat chronic graft versus host disease (cGVHD) in adult allogeneic hematopoietic stem cell transplant patients, but experience in children is limited, perhaps because of lack of pediatric dosing information. In this report, we describe our pediatric and young adult dosing strategy experience in cGVHD. Methods: Ruxolitinib was administered orally at 5 mg twice daily for children ≥25 kg or 2.5 mg twice daily if <25 kg. The dose was halved with concurrent azole administration and increased to a maximum of 10 mg twice daily if tolerated. Responses were evaluated using the 2014 NIH consensus criteria. Phosphorylation of lymphocyte STAT5 following dosing, a surrogate of JAK inhibition, was evaluated by flow cytometry. Results: Twenty patients with a median age 14.6 y (range 5–26 y) received ruxolitinib for severe (n = 9) and moderate (n = 11) cGVHD. Median steroid dose was 0.5 mg/kg/d (range 0.08–1.5 mg/kg/d) at ruxolitinib initiation. Two patients with moderate cGVHD achieved a complete response (CR), while 12 patients achieved a partial response (PR) at a median of 48 d (range 17–98 d) from the first ruxolitinib dose, for an overall response rate of 70%. Eleven patients are maintaining their PRs. pSTAT5 on lymphocytes was absent or decreased (0%–6% events) in 5 evaluated patients, suggesting adequate inhibition. Three patients discontinued ruxolitinib because of neutropenia, thrombocytopenia, or elevated alanine aminotransferase. Four patients developed bacterial infections, and 3 experienced symptomatic viral infections. Two patients died from complications related to progressive severe cGVHD. Conclusions: Ruxolitinib using our dosing strategy demonstrates promise for treating cGVHD in children. Abstract : Supplemental Digital Content is available in the text.